Performance, Breast Morphological and Carcass Traits in the Ardennaise Chicken Breed - Lariviere, J.M.; Farnir, F.; Detilleux, J.; Michaux, C.; Verleyen, V.; Leroy, P. (International Journal of Poultry Science, 2009)
The aim of this study was to quantify performance, breast morphological and carcass traits in Belgium’s most ancient chicken breed: the Ardennaise. Evaluation during growing showed at 84 days of age light as-hatched mean live Body Weights (BW) (1115g ± 221), fairly high Feed Conversion Ratio (FCR) (5.09 ± 0.4) and Liveability (LIV) (92.55% ± 4.6). At 85 days, male and female in vivo breast measurements such as Keel Angle (KA) (67.74-71.82o), Thoracic Circumference (TC) (25.61-28.05 cm), Keel Length (KL) (10.32-11.26 cm) and muscle thickness (TM) (10.70-12.11mm), with associated BW, were all greater in males and significantly different between sexes (p<0.001), except for Chest Width (CW) (4.62-5.35 cm). However, there was no sexual dimorphism for all yield traits. Yields of Eviscerated Carcass (EC) varied from 57.54-59.28%, Thighs and Drumsticks (TD) from 19.37-19.80%, Breast Meat (BM) from 11.02-11.62% and Wings (WI) from 8.67-8.82%. All in vivo measurements, carcass and portions data were lower than those reported mostly for broilers, except similar KA degrees and slightly higher WI. Finally, most of traits studied in the Ardennaise chicken were moderate when compared to those obtained by broilers.